Profile of proinflammatory markers in pregnant women who died of severe COVID-19 - Pablo B. Bautista-García; Mariana Bahena-Campos; Diana H. Alcántara-Rosas (Revista Médica del Hospital General de México)
Introduction: In December 2019, four cases of pneumonia of unknown origin were reported to the World Health Organization (WHO) in China, caused by SARS-CoV-2. In March 2020, the WHO declared the beginning of the COVID-19 pandemic. In COVID-19, a relevant component is vulnerable groups, such as pregnant women representing a special group due to their high mortality secondary to COVID-19. Objective: Describe the association between proinflammatory markers and survival in pregnant women with critical COVID-19, in the intensive care unit (ICU) of the General Hospital of Cholula from January 2020 to 2021. Materials and methods: This is an analytical and cross-sectional observational retrospective study conducted on pregnant women admitted to the ICU. Pregnant women, between 18 and 35 years old, at 30-40 weeks gestation diagnosed with critical COVID-19 were included. Results: It was observed that pregnant women with critical COVID-19 showed increased values of C-reactive protein, leukocytes, D-dimer, and DHL compared to surviving pregnant patients with critical COVID-19; however, no statistical significance was observed for platelet number and fibrinogen. Conclusion: In the case of pregnant women who died from critical COVID-19, there was a significant increase in inflammatory markers, in contrast to what was observed in other studies, no changes in the number of platelets or fibrinogen were observed.